2015
DOI: 10.1155/2015/169841
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial Alterations Are the Main Features in Pulmonary Artery Remodeling due to Long-Term Chronic Intermittent Hypobaric Hypoxia in Rats

Abstract: Long-term chronic intermittent exposure to altitude hypoxia is a labor phenomenon requiring further research. Using a rat model, we examined whether this type of exposure differed from chronic exposure in terms of pulmonary artery remodeling and other features. Rats were subjected to chronic hypoxia (CH, n = 9) and long-term intermittent hypoxia (CIH2x2; 2 days of hypoxia/2 days of normoxia, n = 10) in a chamber (428 Torr, 4,600 m of altitude) for 46 days and compared to rats under normoxia (NX, n = 10). Body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
4
13
0
Order By: Relevance
“…However, nicootinamide adenine dinucleotide phosphatase oxidase plays a crucial role in eNOS uncoupling since it produces reactive oxygen species (Cuzzocrea et al, 2004;Norton et al, 2013). Intolerant rats exposed to CIHH displayed increased O 2 and decreased NO (Siqués et al, 2014;Brito et al, 2015;Lüneburg et al, 2016). In agreement with these studies, our intolerant rats have low NOx levels and a low vascular response to Ach.…”
Section: Cihh Attenuates Ach-induced Vasodilation In Pulmonary Arteriessupporting
confidence: 86%
See 2 more Smart Citations
“…However, nicootinamide adenine dinucleotide phosphatase oxidase plays a crucial role in eNOS uncoupling since it produces reactive oxygen species (Cuzzocrea et al, 2004;Norton et al, 2013). Intolerant rats exposed to CIHH displayed increased O 2 and decreased NO (Siqués et al, 2014;Brito et al, 2015;Lüneburg et al, 2016). In agreement with these studies, our intolerant rats have low NOx levels and a low vascular response to Ach.…”
Section: Cihh Attenuates Ach-induced Vasodilation In Pulmonary Arteriessupporting
confidence: 86%
“…An additional possibility is that CH increases the sensitivity of the contractile apparatus to Ca +2 and mediates this response via activation of the RhoA/Rho kinase (ROK) pathway, and consequently inhibits the myosin light-chain phosphatase, a central component of vascular smooth muscle contraction ( Jernigan and Resta, 2014). However, our study corroborated decreased NOx levels in intolerant animals during CIHH (Siqués et al, 2014;Brito et al, 2015), which could partially explain the increased potassium R MAX .…”
Section: Cihh and The Vasoconstriction Response To Kcl In Spasupporting
confidence: 55%
See 1 more Smart Citation
“…Some studies in humans have demonstrated changes in the right heart circulation that are similar to those occurring in CH, such as a rise in PAP and right ventricular enlargement and/or hypertrophy (Richalet et al, 2002 ; Sarybaev et al, 2003 ; Brito et al, 2007 ). Remodeling of pulmonary vessels has also been demonstrated in animal models (Brito et al, 2015 ). Notwithstanding, there is scarce research assessing these changes over long durations in larger groups of individuals or looking for new potential associations with other physiological and biochemical variables as associated factors.…”
Section: Introductionmentioning
confidence: 98%
“…Currently it is well-established that adaptation (acclimatization) to high altitude both of natural origin and simulated in the hypobaric chamber has a number of beneficial effects on human health, whole body hypoxic tolerance and improvement of physical training (Meerson, 1984 ; Meerson et al, 1996 ; Millet et al, 2013 ). These effects are observed under conditions of chronic mild hypobaric hypoxia (acclimatization mode) and result from reprogramming of the cardio-pulmonary and metabolic processes, including erythropoiesis, vascular remodeling, pulmonary changes and cardiac hypertrophy (Hultgren and Miller, 1967 ; Savourey et al, 2004 ; Brito et al, 2015 ). The integrity of these reactions is called systemic “structural trace of adaptation” due to which the resistance of an organism against any forthcoming hypoxic exposures is achieved along with more general protective effects (Meerson, 1984 ).…”
Section: Hypobaric Hypoxic Preconditioningmentioning
confidence: 99%